TEACHING RECOUNT TEXT THROUGH BRAINSTORMING (A Classroom Action Research at the 8th Grade Students of Madrasah Tsanawiyah Al-Husna Depok) - Yanti - Rosalinah; Tiara Apriella; Aloysius Rangga Aditya Nalendra; Retno Rahayuningsih (LPPM Universitas Bina Sarana Informatika, 2020)
Abstract: Writing is one of skills in language teaching. There are some kinds of writing genres, one of them is Recount Text. Writing a recount text is helping in memorising about an events or experiences in a kind of sequences story by follow the generic structure of recount text, orientations, events, and reorientation. To make the content and purpose of writing recount texts is effectively fulfilled, the students are provided some guidelines and procedures. However, the way teacher provides the guidelines and procedures does not always get the success in teaching and learning writing. The writer used descriptive qualitative method because the data analysis is presented descriptively. This study aims to apply Brainstorming techniques in teaching Recount Text English in 8th grade students at MTs.Al-Husna Depok. The teaching process through; interviews, observation, literature study, and the internet. Moreover, in order to collect the result of the significant differences before and after of using Brainstorming Technique, the writer uses pre-test and post-test during the observation. The research findings include: 1)The students arranged the sentences into a good paragraph by answering the question who, what, when, where, why, and how. At last, for the second trying of using brainstorming, the students did the practice individually. 2)The advantages of teaching recount text through brainstorming are that the writer found that brainstroming could help the students feel at ease while they are writing. The students can manage their time for writing more efficiently. They could produce unpredictable words for their writing since brainstorming helps them generate ideas more effectively and release their anxiety that cause the writer’s block. 3) Using brainstorming technique is very effective in improving the students’ ability in writing recount text for the 8th grade students at MTs. Al-Husna Depok. By using brainstorming, the writer made the students enjoy writing. It because brainstorming is not a difficult technique to be applied. Keyword: Teaching, Speaking, Information Gap Technique